Karakteristik Sosial Masyarakat yang Berpengaruh Pada Tipologi Hunian Warga Desa Polaman Kabupaten Malang - Damayanti, Fifi; Redi Sigit Febrianto (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
The Polaman village society is Javanese. The characteristics of the Polaman village are closely related to the socio-cultural values ​​of the population. The character of the settlement environment is not only influenced by the character of the people who inhabit it but also the natural conditions surrounding it. Humans, the environment, and socio-cultural conditions are three factors that must be understood integrally in understanding humans as a whole. The natural environment around humans provides the carrying capacity for humans to survive and make choices based on their culture. Space is a very important element in architecture. Lay space is interpreted as the physical existence of a three-dimensional object that can be measured length, width, and height. An understanding of space and other related elements such as socio-cultural conditions and psychological conditions in the relationship between individuals and their environment must be present. Based on the typology of housing, there are no striking differences in residential houses between village officials, village elders, and ordinary citizens. The qualitative descriptive method was determined because the researcher wanted to examine the social and cultural characteristics of the community with non-numeric data. Naturalistic or natural paradigms are used in research, where researchers observe without giving an influence, to obtain factual and significant data. The approach used is the phenomenological approach. The observation method used was the passive participatory observation in which the researcher observed the activities of Polaman residents. In this study, the interview method used was a semi-structured depth interview.